THE EFFECT OF SOCIAL MEDIA ON THE BRAND AWARENESS AT HOTELS IN KUTA AREA - Kurniayu Melati; Febianty Febianty (Institut Pariwisata dan Bisnis Internasional, 2016)
Social media is a phenomenon in the last few years that has drawn a lot of attention both to companies and individuals interacting on the networking landscape. Social media has changed the traditional communication between brands and consumers and enabled consumer to make positive as well as negative influence on brand awareness. Many business actor use these social media as a tool to promote their products and make customers aware with their brand. On the other hand, not all that business actors success to market their products and convince the customers. Therefore, it is important for the hotel to know, how to manage communicate in social media seeking to build the brand awareness and positive image for brand. The essence of this study is to research how some hotel can seize the moment of using social media networks to increase brand awareness and brand image. In recent days, social media has taken new forms which have more advantages over the traditional mediums like print media, TV and radio. Marketing communication is becoming precise, personal, interesting, interactive and social. Awareness which include both of recall and recognition become the first step for any move toward a successful market strategy. The Main purpose of this study is to show the role of social media on the brand awareness .The study finding can be used by the hotels to increasing brand awareness through social media. The result of this research is to show that marketing communication (social media ) in a company has an impact to company’s brand awareness. The summary of this research is to get significant information about the effect of social media toward company’s brand awareness through quantitative research method due to the rising of social media .